Awakening of the Self to the Interconnectedness of Things: Stewardship and Caring for Creation through Religious Lens. Review of Religious Self-Cultivation and Environmental Flourishing: A Humanist Relational Approach, by Anthony Le Duc - Nguyen, Vien V. (Studia Ecologiae et Bioethicae, 2024)
In Anthony Le Duc’s book Religious Self-Cultivation and Environmental Flourishing: A Humanist Relational Approach, it is emphasised the significance of spiritual formation in fostering ecological awareness and stewardship of our common home. The review shows how diverse faith traditions—from Theravada Buddhism and Confucianism to Islam and Christianity—provide ethical guidance and practices that nurture harmonious relations between humanity and the natural world, highlighting the interconnectedness of all life. In its second part, the book underscores the value of intercultural and interreligious dialogue and introduces the concept of “inter-creationality” as a basis for collaborative environmental action.